TB or not TB? Diagnostic Sensitivity, Specifity and Interobserver Agreement in the Radiological Diagnosis of Pulmonary Tuberculosis in Children - Brinkmann, Folke; Hofgrefe, Jana; Ahrens, Frank; Weidemann, Jürgen; Berthold, Lars Daniel; Schwerk, Nicolaus (Klinische Pädiatrie, 2024)
Background The differentiation between latent tuberculosis infection (LTBI) and tuberculosis (TB) relies on radiological changes. Confirming the diagnosis remains a challenge because typical findings are often missing in children. This study evaluates diagnostic sensitivity, specifity and interobserver agreement on the radiological diagnosis of TB by chest-x-rays in accordance to professional specialization and work experience.Methods Chest x-rays of 120 children with proven tuberculosis infection were independently evaluated by general radiologists, paediatric radiologists and paediatric pulmonologists. Results were compared to a reference diagnosis created by group of experienced paediatric radiologists and paediatric pulmonologists. Primary endpoints were diagnostic sensitivity and specificity and interobserver variability defined as Krippendorfs alpha of thesel groups compared to the reference diagnosis.Results Of the 120 chest x-rays 33 (27,5%) were diagnosed as TB by the reference standard . Paediatric pulmonologist had the highest diagnostic sensitivity (90%) but were less specific (71%) whereas general radiologist were less sensitive (68%) but more secific (95%). The best diagnostic accuracy was achieved by pediatric radiologists with a diagnostic sensitivity of 77% and specificity 95% respectively.Conclusions We demonstrated significant interobserver variability and relevant differences in sensitivity and specificity in the radiological diagnosis of TB between the groups. Paediatric radiologists showed the best diagnostic performance. As the diagnosis of pulmonary TB has significant therapeutic consequences for children they should be routinely involved in the diagnostic process.
Keywords: children; tuberculosis; radiology; intraobserver variability